Movin' into the fast lane on the information superhighway. (Crisis (00111422), 1995)
Focuses on the importance of fair access to the Internet. Comparison of the number of whites and blacks with access to computers and telephones; Concern over the possibility that blacks will be left behind by Internet technology; Problems related to the acquisition and provision of necessary hardware for access.